Sostenibilidad en las instituciones microfinancieras: ¿la regulación hace alguna diferencia? - Leveau, Andrea (2007)
Microfinance is a tool to solve problems of the limited access to finance services among low-income earners and thereby promote inclusion. It is important that entities offering such services are sustainable, both currently and into the future. Today some microfinance institutions believe that the way to obtain better financial results and to reach poor clients is through regulation. This paper has investigated the factors that determine sustainability (measured byself-sufficiency) and the extent to which regulation matters. Microfinance also has a social objective, and we seek to determine whether the interest variable influences performance. Using a simple theoretical model, we offer a method to analyze the financial and social objectives. Using statistical and econometric tools, the article looks at the differences between the diverse types of microfinance entities (regulated and non-regulated). It finds that regulation is less significant in financial sustainability and social outreach since any improvement in the results of the entity depends of the characteristics of the institution itself. However, there could be indirect benefits from regulation if regulation is the only way for IMFs to access to more financial funding.